study of charge exchanging in atom-atom scattering - Mustafaa Abed Alsattar (University of Thi-Qar Journal of Science, 2019)
The adsorption of atoms on the surface and its effect on the charge transfer process in the hyper – thermal energies regime, is one of the most important subject in surface physics especially in studying the effect ofelectron – phonon coupling. And to study this effect due to the recoil of the adatom through out thescattering of atom from surface covered with low coverage , Anderson Hamiltonian is used whichincorporates the interaction of the scattering atom with the adatom and the interaction of the adatom with thesurface atoms. Since the atom is scattered from the adatom and the charge transfer happens through out resonance andquasi-resonance charge transfer. The Hamiltonian incorporates also the electron-phonon coupling interaction.The system of equations for scattered atom-adatom/ surface is treated using the wide band approximation.The system of equations are solved numerically using six-order Runge-Kutta method with the accuracy ischecked at each time. The treatment is applied to real system, that is Li-K/W, since the ionization probabilityof the scattered atom , the occupation number of the adatom and the number of phonons on the adatom arecalculated as function of all the variables that related to the treatment such as the initial energy of thescattered atom . The effects of the adatom-adatom interaction when the adatom are identical or not areinvestigated. In addition, it is found that the ionization process is enhanced when the adatoms are notidentical. The ionization probability and the number of phonons are calculated as a function of couplingstrengths variation. The maximum number of phonons, that generated due to recoil, is calculated as a function of the initial energy of the scattered atom and it is found that our calculations are within